High-entropy approach to double perovskite cathode materials for solid oxide fuel cells: Is multicomponent occupancy in (La,Pr,Nd,Sm,Gd)BaCo2O5+δ affecting physicochemical and electrocatalytic properties? - Dąbrowa, Juliusz; Stępień, Anna; Szymczak, Maria; Zajusz, Marek; Czaja, Paweł; Świerczek, Konrad (Frontiers in Energy Research, 2022)
High-entropy (La,Pr,Nd,Sm,Gd)BaCo2O5+δ double perovskite-type oxide having an equimolar, high-entropy, A-site-layered arrangement of cations is synthesized for the first time. A modified Pechini method, followed by calcination and sintering at 1,100°C helps in obtaining a single-phase, homogenous material with tetragonal I4/mmm symmetry. In situ X-ray diffraction and dilatometric studies show excellent phase stability up to 1,100°C in air, with the average thermal expansion coefficient of 23.7∙10–6 K−1 within the 25–1,100°C range. Total electrical conductivity of the metallic character exceeds 1,600 S cm−1 at room temperature. Equilibrated oxygen content at room temperature is determined as 5.69. The cathodic polarization resistance of the (La,Pr,Nd,Sm,Gd)BaCo2O5+δ layers, manufactured on the La0.8Sr0.2Ga0.8Mg0.2O2.8 (LSGM) solid electrolyte of proved inertness, is as low as 0.037 Ω cm2 at 900°C, and 0.175 Ω cm2 at 750°C. The determined value of the power density in the LSGM-based, electrolyte-supported (thickness ca. 200 μm) fuel cell reaches 857 mW cm−2. These results indicate possible applicability of the developed cathode material for solid oxide fuel cells, making it also one of the best-performing high-entropy air electrodes reported until now. However, the determined physiochemical characteristics of the material indicate a relatively limited influence of the high-entropy A-site arrangement in comparison to the conventional analogs, including the synthesized Nd0.88Sm0.12Co2O5+δ composition, characterized by the same effective radius of the lanthanide cations.